Description of an endemic and endangered new Sympetrum species (Odonata: Libellulidae) from the subtropical area of Taiwan - Tang, Hsin-Chieh; Yeh, Wen-Chi; Chen, Szu-Lung (Zootaxa, 2013)
Sympetrum nantouensis sp. nov. collected from Nantou, Central Taiwan, is described and figured, with remarks on its ecology and oviposition behaviour. Judging from penile structure, it is considered to belong to the infuscatum-group, whose members are defined here by penile characters. In the infuscatum-group, S. nantouensis is most similar to S. risi Bartenev, but they are probably not very closely related to each other. Sympetrum nantouensis differs from S. risi mainly in having beak-like cerci, well-lineated black and pale yellow pterothorax, and penile 4th segment with longer and apically upcurved cornua. This new species is distinct among its congeners in view of both biogeography and morphology because of its confined and peripheral existence and the odd shape of its cerci. All type specimens will be deposited at the Insect Collection of TFRI.